Characterizing hepatocellular carcinoma stem markers and their corresponding susceptibility to NK-cell based immunotherapy - Chiang, Jason; Chen, Po-Chun; Pham, Janet; Nguyen, Cat-Quynh; Kaur, Kawaljit; Raman, Steven S.; Jewett, Anahid (Frontiers in Immunology, 2023)
Introduction: Hepatocellular carcinoma (HCC) is the most common primary liver cancer and is the fourth-leading cause of all cancer-related deaths around the world. Liver transplantation, surgery, and local ablation are curative therapies for early-stage HCC. However, post-treatment outcomes can vary based on histopathologic stage. Poorly-differentiated HCC are associated with higher rates of tumor progression and lower overall survival compared to well-differentiated HCC after therapy. In this study, we aimed to characterize the cancer stem cell (CSC) profile of histopathologically-proven well and poorly-differentiated HCCs based on their surface markers and susceptibility to NK cell-mediated cytotoxicity. Methods: Flow cytometry was used to quantify differential expression of MHC-class I, CD54, and CD44 between well- and poorly-differentiated HCCs. Primary untreated NK cells, IL-2 stimulated primary NK cells, and supercharged (sNK) cell-mediated cytotoxicity was assessed against well- and poorly-differentiated HCCs. IFN-γ supernatant from each respective NK cell experimental arm was also used to induce differentiation of HCCs. Finally, we characterized the temporal NK effector cell cytotoxicity using real-time quantitative analysis of imaging and impedance (eSight study). Results: Poorly-differentiated HCCs demonstrated low surface expression of MHC-class I and CD54, and high expression of CD44. Treatment of NK cells secreted IFN-γ or IFN-γ cytokine induced differentiation in HCCs. Poorly-differentiated HCCs in comparison to well-differentiated HCC were more susceptible to NK cell-mediated cytotoxicity in primary NK cells, IL-2 stimulated primary NK cells, and sNK cells. sNK cells induced significantly higher cytotoxicity against well-differentiated HCCs in comparison to untreated or IL-2-stimulated primary NK cells. These findings were recapitulated with real-time quantitative imaging analysis. Conclusions: Poorly-differentiated HCCs were found to have surface marker patterns of CSCs, making them highly susceptible to NK cell-based immunotherapy. NK-cell based therapy can potentially be leveraged as a neoadjuvant or adjuvant therapy in poorly-differentiated HCCs. Supercharged NK cells, which can be rapidly expanded to therapeutic levels, are uniquely capable of lysing both poorly- and well-differentiated HCCs. This finding suggests that sNK cells not only exhibit enhanced features against NK cells’ targets but also are capable of activating T cells to induce cytotoxicity against well-differentiated HCCs with high expression of MHC class I.